Validity and reliability of archery sport arm muscle endurance training program based on body weight training - betrix; Doni Pranata; Galih Dewanti; Putri Famelia; Zhanneta Kozina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Archery is a sport that shoots arrows using a bow. The most important physical aspect of archery is endurance. Purpose: This study aims to examine the validity and reliability of the contents of the arm muscle endurance training program. The participants involved in this study were 5 physical trainers and 2 nationally licensed archery trainers. Some documents are also used in this research. The approach used is a mixed qualitative and quantitative approach. This study was divided into four stages: (1) qualitatively analyzing e-books, textbooks, and related articles, (2) evaluating programs using the Delphi technique, which involves experts rating questionnaires on a scale of 1 to 5 until a consensus is obtained, (3) content validity testing using the CVR formula, (4) reliability testing using Cronbach alpha and ICC. Content validity and Cronbach alpha value, based on the findings it can be stated that the program has a very good validity and reliability value and is worthy of being given to athletes. Based on the results of the content validity test and the reliability test it can be stated that the arm muscle endurance training program has a good value, this shows that it can be applied when training archery athletes.